Scalar-Torsion Theories in Four Dimensional Static Spacetimes - Mulyanto .; Fiki Taufik Akbar; Bobby Eka Gunara (Indonesian Journal of Physics, 2021)
In this paper, we consider a class of static spacetimes scalar-torsion theories in four dimensioanal static spacetimes with the scalar potential turned on. We discover that the 2-dimensional submanifold must admit constant triplet structures, one of which is the torsion scalar. This indicates that these equations of motion can be reduced to a single highly non-linear ordinary differential equation known as the master equation. Then, we show that there are no exact solution of the scalar-torsion theory in four dimensions considering the Sinh-Gordon potential.